2017
DOI: 10.1007/s13205-017-0763-0
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant expression, characterization and application of a dihydrolipoamide dehydrogenase with diaphorase activity from Bacillus sphaericus

Abstract: Diaphorases are flavin-containing enzymes with potential applications in biotransfomation reactions, biosensor design and in vitro diagnostic tests. In this communication, we describe recombinant expression, characterization and application of a lipoamide dehydrogenase (DLD) with diaphorase activity from a strain of Bacillus sphaericus. The DLD gene consisting of 1413 bp encoding a protein of 470 amino acids was expressed in Escherichia coli BL21 (DE3) and the recombinant enzyme was characterized. B. sphaericu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Tamai et al (2016) suggested that diaphorase is involved in bromate reduction by strain Br-6, and that strain Br-6 has multiple isoforms of diaphorase 3 . Some dihydrolipoyl dehydrogenase (DLD) enzymes have NADH-dependent diaphorase activity 19 . The Br-6 genome contains the lpdC gene, which encodes DLD (locus_tag: Br6_03586; UniProt: E4W8R5).…”
Section: Resultsmentioning
confidence: 99%
“…Tamai et al (2016) suggested that diaphorase is involved in bromate reduction by strain Br-6, and that strain Br-6 has multiple isoforms of diaphorase 3 . Some dihydrolipoyl dehydrogenase (DLD) enzymes have NADH-dependent diaphorase activity 19 . The Br-6 genome contains the lpdC gene, which encodes DLD (locus_tag: Br6_03586; UniProt: E4W8R5).…”
Section: Resultsmentioning
confidence: 99%
“…The optimum temperature of puri ed rDIA was determined by measuring its activity at a series of temperatures of 20,25,30,35,37,40,45,50,55,60,65,70,75, and 80°C. For calculating its thermostability, rDIA was pre-incubated in 0.2 M potassium phosphate buffer (pH 6.5) at a series of gradient temperatures (treated by PCR instrument) of 30.3, 32.1, 34.4, 36.7, 40.1, 43.3, 46.7, 50.0, 53.4, 55.0, 58.4, 59.9, 65.0 and 70°C for 40 min.…”
Section: Effect Of Temperature On the Activity And Stability Of Rdiamentioning
confidence: 99%
“…Both ferrocenium compounds and hexacyanoferrate (III) of this kind diaphorase could be used as electron transfer mediators and co-immobilization with several dehydrogenases in a membrane electrode format yielded sensors (Antiochia et al 2015). Lipoamide dehydrogenase (DLD) with diaphorase activity, was successfully heterologous expressed and puri ed from E. coli, and the suitable kinetic features of DLD could make this biocatalyst useful for application as a diagnostic enzyme (Kianmehr et al 2017). However, there are still some disadvantages such as low yield (Klyachko et al 2005), low activity ) and poor stability (Kianmehr et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with other biological insecticides, Bs has several advantages, including low environmental toxicity due to the high specificity of Bs toxins, high levels of efficacy, and environmental persistence. Meanwhile, the use of Bs recombination agents can also extend the mosquito-killing spectrum, prolong the action time, and improve the insecticidal efficacy [ 9 11 ]. Furthermore, it was reported that Bs successfully decreased the spread of mosquito-borne diseases in epidemic areas [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%